2021
DOI: 10.3389/fneur.2021.638904
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lower Limb Constraint Induced Movement Therapy in People With Stroke: A Systematic Review and Meta-Analysis

Abstract: Background: Constraint induced movement therapy (CIMT) is effective at improving upper limb outcomes after stroke.Aim: The aim of this study was to carry out a systematic review and meta-analysis of the effects of lower limb CIMT studies of any design in people with stroke.Materials/ Method: PubMED, PEDro, OTSeeker, CENTRAL, and Web of Science were searched from their earliest dates to February 2021. Lower limbs CIMT studies that measured outcomes at baseline and post-intervention were selected. Sample size, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 44 publications
2
16
1
Order By: Relevance
“…Our findings were comparable to the conclusions of the study by Abdullahi et al [ 17 ], which focused exclusively on the effects of lower extremity CIMT on the stroke population, including multiple lower extremity functional components such as gait, lower extremity motor function, balance, functional mobility, and quality of life. Their effect size from the meta-analysis was 0.62 (95% CI [−0.54 to 1.78]) for balance and −0.53 (95% CI [−3.61 to 2.55]) for functional mobility, showing a statistically insignificant effect of lower extremity CIMT on both balance and functional mobility.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our findings were comparable to the conclusions of the study by Abdullahi et al [ 17 ], which focused exclusively on the effects of lower extremity CIMT on the stroke population, including multiple lower extremity functional components such as gait, lower extremity motor function, balance, functional mobility, and quality of life. Their effect size from the meta-analysis was 0.62 (95% CI [−0.54 to 1.78]) for balance and −0.53 (95% CI [−3.61 to 2.55]) for functional mobility, showing a statistically insignificant effect of lower extremity CIMT on both balance and functional mobility.…”
Section: Discussionsupporting
confidence: 91%
“…Previous reviews of CIMT involved many impairment measures, such as range of motion and spasticity, and activity measures, such as gait and upper and lower extremity function, though many did not consider the crucial components of balance and functional mobility [ 17 , 37 , 38 , 39 , 40 ]. The current systematic review with meta-analysis of RCTs is thus the first to focus on the effects of lower and upper extremity CIMT on balance in the stroke population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study where muscle synergies were adopted to stratify stroke patients, synergies distributed coherently according to the Fugl-Meyer scale and Reaching Performance Scale, indicating that synergies convey similar underlying information [ 19 ]. Some other studies showed that muscle synergies and clinical scales were weakly correlated, and that stroke does not affect the inner structure of synergies, but rather their temporal recruitment [ 20 , 21 ]. There has also been evidence that synergies can improve in terms of their timing and organization by specific targeted therapies, including robot therapy or virtual reality treatment [ 15 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%